The Influence of Trust, Perceived Usefulness, Perceived Ease of Use, Perceived Risk, and Perceived Security on Continuance Intention e-wallet ShopeePay on Generation Z in Padang City mediated by Consumer Attitude and Consumer Engagement: Pengaruh Trust, Perceived Usefulness, Perceived Ease of Use, Perceived Risk dan Perceived Security terhadap Continuance Intention e-wallet ShopeePay pada Generasi Z di Kota Padang yang dimediasi oleh Consumer Attitude dan Consumer Engagement - Lathifah Decdebels Aulia Rahmi; Arief Maulana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the influence of trust, perceived usefulness, perceived ease of use, perceived risk and perceived security on the continuance intention of ShopeePay e-wallet with consumer attitude and consumer engagement as mediators. An online survey was conducted to collect data from 202 Shopeepay users in Padang City. Data analysis used Partial Least Squares Structual Equation Modeling (PLS-SEM) to evaluate the relationship between variables. The results showed that Trust and Perceived Risk each had no significant effect on Consumer Attitude. In addition, Perceived Usefulness, Perceived Ease of Use, and Perceived Security were found to have a positive and significant effect on Consumer Attitude. Furthermore, consumer attitude was found to have a positive and significant effect on Consumer Engagement. And Consumer Engagement was found to have a positive and significant effect on Continuance Intention. Finally, Consumer Attitude was found to have a positive and significant effect on Continuance Intention.